Yakuza [videorecording] (Quezon City ABS-CBN News and Public Affairs, 1990)
Operations of Yakuza, a mafia oriented organization that drives at illegal activities ranging from prostitution to drugs; Options of the Aquino government in determining the faith of the military bases in the country; Profile of Manoling Morato during his term as chairman of the MTRCB.
Yakuza / producer, Jake Maderazo (25 min.) -- The U.S. bases : options in the final countdown / producer, Marlen Ronquillo (18 min.) -- Uncensored / producer, Veronica Pedrosa (17 min.)
VHS.
Keywords: Morato, Manuel; Yakuza; Military bases, American -- Philippines; Motion pictures -- Censorship -- Philippines